Research of the Path Optimization for the NC Planing Process of the Spur Face-gear - Qian Lulu; Yang Xiaoyu; Tang Jinyuan (Jixie chuandong)
The principle of the NC planing process of the spur face-gear is briefly introduced,the equations of the tooth profile and the tooth cutter are derived,the mathematical relation between the tooth cutter angle and the allowance is established,and then,the machining path of the NC planing of the spur face-gear is optimized. With the comparison result between the optimized machining path and the previous one,it is indicated that the proposed optimized method can shorten the feeding times by 50%. Finally,the optimized machining path is simulated in NC codes with the Vericut software,which shows that the optimized machining path method for the NC planing of the spur face-gear is feasible,efficient and can meet the precision requirement.